Bioaugmentation performance for moving bed biofilm reactor (MBBR) treating mariculture wastewater by an isolated novel halophilic heterotrophic nitrification aerobic denitrification (HNAD) strain (Zobellella B307). (1st January 2023) - Xiang, Zhuangzhuang; Chen, Xi; Bai, Jie; Li, Bohan; Li, Hui; Huang, Xiao
Abstract: Moving bed biofilm reactor (MBBR) demonstrates weak nitrogen removal for mariculture wastewater treatment under high salinity environment. An isolated novel halophilic heterotrophic nitrification aerobic denitrification (HNAD) strain ( Zobellella B307 ) was applied in MBBR process to enhance nitrogen removal. Results showed that strain Zobellella B307 could remove 90.9% ammonia nitrogen (NH4 + -N) and 97.1% nitrate nitrogen (NO3 − -N) after 10 h cultivation, and strong resistance to salinity variation (high growth and nitrogen removal efficiency with salinity of 65‰) was observed. Besides, the chemical oxygen demand (COD), NH4 + -N and NO3 − -N removal reached 95.6%, 94.4% and 85.7% with the strain added into MBBR process. In addition, microbial community structure analysis reflected that the strain Zobellella B307 successfully proliferated (the relative abundance increased to 2.33%). The HNAD bacteria abundance increased and dominated during the nitrogen removal process with the strain inoculation. A microbial functional analysis revealed that the main dominant functional categories (carbohydrate metabolism and amino acid metabolism) increased with the bioaugmentation of strain Zobellella B307, thus improving the nitrogen removal. Graphical abstract: Image 1 Highlights: A HNAD strain was isolated with more than 90% NH4 + -N and NO3 − -N removal rate. The HNAD strain ( Zobellella B307) was successfully dominated in MBBR. The HNAD strain enhanced COD and nitrogen removal performance. Nitrogen metabolism functional genes increased with Zobellella B307 inoculation.